Microvesicle subsets in sepsis due to community acquired pneumonia compared to faecal peritonitis - Lashin, H; Nadkarni, S; Oggero, S; Jones, H; Knight, J; Hinds, C; Perretti, M (Lippincott, Williams & Wilkins, 2017)
Microvesicles (MV) act as a non-soluble means of inter-cellular communication, with effector roles in disease pathogenesis and potentially as biomarkers. Previously, we reported that neutrophil MV expressing alpha-2-macroglobulin (A2MG) are protective in experimental sepsis and associate with survival in a small cohort of patients with sepsis due to community acquired pneumonia (CAP).To characterise MV profiles in sepsis due to CAP or faecal peritonitis (FP) and determine their relation to outcome. To investigate the effects of novel sepsis treatments (granulocyte-macrophage colony stimulating factor (GM-CSF) and interferon-υ (IFN-γ)) on MV production and functions in-vitro.Flow cytometry analysis of MV identified the cell of origin and the proportion of A2MG expression in the plasma of patients with sepsis secondary to CAP (n = 60) or FP (n = 40) and compared to healthy volunteers (HV, n = 10). The association between MV subsets and outcome was examined. The ability of GM-CSF and IFN-γ on A2MG MV production from whole blood was examined together with the assessment of their effect on neutrophil and endothelial functions.Circulating cell-derived and A2MG MV were higher in CAP compared to FP and HV. A2MG MV were higher in survivors of CAP, but not in FP. GM-CSF and IFN-γ enhanced A2MG MV production, with these MV eliciting pathogen clearance in vitro.Plasma MV profiles vary according to the source of infection. A2MG MV are associated with survival in CAP but not FP. We propose specific MV subsets as novel biomarkers in sepsis and potential effector for some of the actions of experimental therapeutic interventions.